Synthesis and characterisation of a photoresponsive four-armed graft copolymer prepared from coumarone and methyl methacrylate - Bezgin, F; Demirelli, K (Pigment & resin technology, 2014)
Purpose - This paper aims to a newly designed photoresponsive four-armed graft copolymer was synthesised and characterised. The synthesised polymer contains photochemical group and a greater part of the cross-linkable functional group which is not affected by short wavelength when subject to under ultraviolet (UV) irradiation in film status. Design/methodology/approach - The four-armed macroinitiator was prepared by reacting diethanol amine with poly [methyl-2-chloro-4-{7-(chloroacetyl) oxy]-2-oxo-2H-chromen-4-yl}-2-methylbutanoate] and acylating the product with chloroacetyl chloride. A grafting reaction with n-butyl methacrylate was carried out in the presence of the four-armed macroinitiator and the catalyst CuBr/2, 2'-bipyridyne at 90°C. All of the synthesised polymers were structurally characterised by Fourier transform infrared spectroscopy (FT-IR) and Hydrogen-1 Nuclear Magnetic Resonance (1H-NMR) spectra. Gel permeation chromatography was used to obtain the molecular weights of polymer. Findings - 1H-NMR, FT-IR and ultraviolet-visible (UV-Vis) spectroscopy demonstrated that the four-armed macroinitiator and the graft copolymer was successfully synthesised. The end-functionalised poly(methyl methacrylate) with 7-hydroxyl-4-chloromethyl coumarone was irradiated at the wavelength larger than 300 nm to create the cyclobutane ring in between the 7-hydroxyl-4-chloro methyl coumarone unities. To characterise the polymer and show the transformation of coumarone unities into photodimers, 1H-NMR, FT-IR and UV-Vis spectroscopy were used. Research limitations/implications - Graft copolymer containing coumarone has involves photocrosslinkable functional group, in which reactive functional group has attracted great interest from both industrial and academic fields. Their synthesis provides the opportunity for a compatible modification of the graft copolymer structure to develop adapted macromolecules for a range of end practices. Practical implications - A photoresponsive graft copolymer can have a role in an active area of polymer chemistry research due to its uses in the areas of photolithography, liquid crystal, non-linear optical materials, laser dyes, fluorescence materials and future microelectronics. Originality/value - Graft copolymers containing a photocrosslinkable functional group, and a star polymer may be prepared using the method described in this paper and then used in technological applications. The method discussed here also allows photoinduced reversible self-healing in solid polymers.